2017
DOI: 10.1007/s11748-017-0873-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct perfusion of the carotid artery in patients with brain malperfusion secondary to acute aortic dissection

Abstract: Aggressive direct reperfusion of the carotid artery before the aortic repair may reduce neurological complications in patients with preoperative brain malperfusion secondary to acute aortic dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 16 publications
0
35
0
Order By: Relevance
“…We reported our first successful case as a simple bypass circuit between the common FA and right CCA performed in the emergency room 30 . We found that lower reperfusion flow to the CCA was beneficial in terms of electroencephalographic recovery and brain water contents.…”
Section: Discussionmentioning
confidence: 90%
“…We reported our first successful case as a simple bypass circuit between the common FA and right CCA performed in the emergency room 30 . We found that lower reperfusion flow to the CCA was beneficial in terms of electroencephalographic recovery and brain water contents.…”
Section: Discussionmentioning
confidence: 90%
“…Extracorporeal femoral-carotid shunting for maintenance of antegrade cerebral perfusion has previously been reported, but with important differences. 1 , 2 , 3 , 4 These reports used either surgical bypass or surgical conduits connected to tubing and a centrifugal pump. Comparatively, our approach using endovascular sheaths eliminates the need for two surgical anastomoses and offers the potential for a percutaneous femoral approach, eliminating the need for groin exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of brain complications in acutely dissected patients is largely due to a compressed true lumen by the false lumen, static or dynamic [7]. It is often multifactorial, frequently coexisting with circulatory collapse, sequelae of acute hypoxia, and thromboembolism originating from the false lumen [7].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of brain complications in acutely dissected patients is largely due to a compressed true lumen by the false lumen, static or dynamic [7]. It is often multifactorial, frequently coexisting with circulatory collapse, sequelae of acute hypoxia, and thromboembolism originating from the false lumen [7]. However, as a main cause of postoperative neurological deficiency, the possibility of thromboembolism owing to thrombi derived from a thrombosed false lumen has been noted [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation